Exploring the Linguistic Aspects of Translating and Validating the Mountain Province State University’s Vision, Mission, Thrusts and L2 Core Values: A Comprehensive Analysis - Fagsao, Jonnelle D.; Mi-Ing-Docallas, Julie Grace; Cue, Edgar G. (An Overview of Literature, Language and Education Research Vol. 9, 2025)
Analyzing qualitative-translation research is a challenging process that requires skills and abilities in both the source and target languages as well as a variety of approaches and procedures in the art of translating. The research team, together with a few additional chosen external validators and translators, conducted a translation of the MPSU VMT (Mountain Province State University – Visions, Missions, and Thrusts) and Core values from source language (L2) to target language (L1). This study discusses and explores the cultural linguistic dimension involved in the translation process. An essential tactic in the L2-L1 translation process was the bilingual translation techniques that were employed, which were obtained from local translators. According to the study's findings, translation may help the college’s students and stakeholders develop their understanding and translation abilities based on the translated VMT and Core Values. Therefore, the outcome suggests that, in response to the AACUP's (Accrediting Agency of Chartered Colleges and Universities in the Philippines) recommendations and for the benefit of the stakeholders, the verified translation from the research team and selected external validators be approved.